Perancangan Alat Pengering Kerupuk dengan Menggunakan Pemanas Heater - Mohammad Sandoyo Adamsyah; Mulyadi Mulyadi (Universitas Muhammadiyah Sidoarjo, 2019)
Drying is the process of reducing water content to reach a certain moisture content. The drying process of mussel cauliflower in Balongdowo village still relies on sunlight in the drying process. Drying with this process is considered to be less efficient because when the hot rainy season the sun is unpredictable and requires extensive land in the drying process. To overcome this problem, in this final project, the title of the design of cracker dryer is taken using heater heater. Which is expected to increase effectiveness and productivity when the rainy season arrives can also reduce the time and production costs. The method used to solve these problems is to use the bootroyd design method which is designing a dryer that consists of the main components of the drying chamber, conveyor, drive motor and gearbox. The results of the test showed that the drying time of 76 seconds reduced the initial water content of 70% reduced to 15% the water content contained in crackers.